Efektivitas Penggunaan Unmanned Aerial Vehicle (UAV) dalam Strategi Kontra-Terorisme Amerika Serikat di Pakistan (2004-2012) - Irfan, Egalita (Global: Jurnal Politik Internasional, 2014)
Unmanned Aerial Vehicle (UAV) is an armed unmanned plane, which is also one of the most advanced technologies developed by the United States. UAV is more superior compared with other kinds of weapon. Currently, it is used in many parts of the world as a part of the United States' counter-terrorism measure. However, the use of UAV in Pakistan since 2004 to 2012 does not successfully reduce the number of terrorist attack that happens on that country. This research aims to figure out the reasons behind this failure through the use of congruence in retrospective. The results show that the failure of UAV relies upon 3 factors: (1) US did not really understand the characteristic of targeted terrorist organizations, (2) there is a mistake in the decision making based on the intelligence cycle, and (3) the nonexistent of local society's support.